2022
DOI: 10.1021/acsami.2c18074
|View full text |Cite
|
Sign up to set email alerts
|

BINOL-Containing Chiral Porous Polymers as Platforms for Enantiorecognition

Abstract: The enantioselective discrimination of racemic compounds can be achieved through the design and preparation of a new family of chiral conjugated BINOL−porous polymers (CBPPs) from enantiopure (R)-or (S)-BINOL derivatives and 1,3,5-tris(4-phenylboronic acid)benzene or 1,3,5-tris(4-ethynylphenyl)benzene, 1,3,5triethynyl-2,4,6-trifluorobenzene, and tetra(4-ethynylphenyl)methane as comonomers following Suzuki−Miyaura and Sonogashira−Hagihara carbon−carbon coupling approaches. The obtained CBPPs show high thermal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…When ( S )-6,6′- t Bu 2 BINOL diethyl ether was treated with bromine in CH 2 Cl 2 solution at −78 °C, ( S )- 99 with 4.4′-dibromination was obtained in 99% yield . The cross-coupling reaction of ( S )- 99 and its adamantanyl analogue ( R )- 100a with aryl tris-boronic acids and aryl tris- or tetra-terminal alkynes were used to make chiral porous polymers such as ( R )- 100b for enantioselective fluorescent recognition of limonene, α-pinene, and a chiral amine.This paper reports that the bromination of 6,6′- t Bu 2 BINOL diethyl ether occurs at the 4,4′-position, which is in contrast to the reported 3,3′-dibromination of 6,6′- t Bu 2 BINOL to form ( S )- 122 , where a single crystal X-ray analysis has confirmed the structure (see Scheme ).…”
Section: Electrophilic Substitution At 4-positionmentioning
confidence: 99%
“…When ( S )-6,6′- t Bu 2 BINOL diethyl ether was treated with bromine in CH 2 Cl 2 solution at −78 °C, ( S )- 99 with 4.4′-dibromination was obtained in 99% yield . The cross-coupling reaction of ( S )- 99 and its adamantanyl analogue ( R )- 100a with aryl tris-boronic acids and aryl tris- or tetra-terminal alkynes were used to make chiral porous polymers such as ( R )- 100b for enantioselective fluorescent recognition of limonene, α-pinene, and a chiral amine.This paper reports that the bromination of 6,6′- t Bu 2 BINOL diethyl ether occurs at the 4,4′-position, which is in contrast to the reported 3,3′-dibromination of 6,6′- t Bu 2 BINOL to form ( S )- 122 , where a single crystal X-ray analysis has confirmed the structure (see Scheme ).…”
Section: Electrophilic Substitution At 4-positionmentioning
confidence: 99%
“…BINAPcontaining POFs were prepared using copper-catalyzed alkyne−azide click reaction starting from diethynyl 2,2′-bis(diphenylphosphino)-1,1′-binaphthlyl (BINAP) compound (Scheme 3D) [51]. POFs composed of BINOL building blocks have been prepared using various couplings [52], such as FeCl3-induced oxidative homocoupling polymerization (Scheme 3E) [53] or Suzuki coupling (Scheme 3E) [54]. Proline-functionalized building The most straightforward approach is (i) using chiral building blocks as the starting materials, as this approach ensures the full incorporation of the chiral moieties into the material [33][34][35][36][37][38].…”
Section: Chiral Building Blocksmentioning
confidence: 99%
“… 9 Currently, many studies have shown that, the host molecule selectively binds to the enantiomer of the guest molecule through non-covalent interactions such as hydrogen bonding, 10 metal coordination, π–π packing, 11 and/or electrostatic interactions. 12 So a number of chiral systems are reported for enantioselective recognition and separation, such as chiral metal–ligand complexes, 13 chiral polymers, 14 micelles, 15 and vesicles. 16 Supramolecular chiral polymers, as a good host material, provide more possibilities for chiral recognition.…”
Section: Introductionmentioning
confidence: 99%